Production of Phytase, Amylase and Cellulase by Aspergillus niger, Neurospora crassa, and Rhizophus oryzae on Sargassum and Rice Bran Under Solid State Fermentation - Atit Kanti (ANNALES BOGORIENSES, 2015)
The objective of study was to produce amylase, cellulase and phytase on sargassum and rice bran on solid state fermentation using Aspergillus niger, Neurospora crassa and Rhizophus oryzae. Media for solid state fermentations composed of dried sargassum and rice bran. The effect of particle of sargassum, initial moisture content on phytase, amilase, and cellulase were evaluated. Optimum enzyme activity of phytase, amylase and cellulase were obtained after 4 days fermentation at 30°C, and initial moisture content was adjusted to 60%. The optimum particle size of dried sargassum attaining the highest enzyme activity was 25 mesh. Best formula forenzymes production was at the ratio of 4:6 (w/w) of Sargassum spinosum (SS) and rice bran (RB) respectively. At this formula highest phytase activity was obtained by Aspergillus niger, cellulase by Rhizopus oryzae, and amylase by Neurospora crassa. Media composed of sargassum and rice bran can be used for phytase, amylase and cellulase production.